KETERAMPILAN MANAJERIAL DAN PENGEMBANGAN KARIR PENGARUHNYA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN MAINTENANCE PT. GLOBAL MAKARA TEKNIK SITE BRE RANTAU KABUPATEN TAPIN) - Akhmad Jailani Fahmi; Rahmi Widyanti; Maskur Maskur (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
This research discusses the discussion of theory, discussion of experts, discussion of researchers based on their experience, then developed into a debate - renewal developed - the solution requested to obtain justification (verification) in the form of empirical supporting data in the field. This study aims to learn more about Managerial Skills and Career Development Influence on Employee Performance (Study on Maintenance Employees of PT. Global Makara Teknik Site BRE Rantau Tapin Regency) in South Kalimantan, The method used in this study is a quantitative method, with as much as 54 assistance, a sample of 54 people and data analysis techniques using the research instrument validity test, reliability test, classic assumptions and using multiple linear regression, The results of this study indicate that the variable managerial ability individually to the Maintenance Performance of PT. The Makara Global Bara Engineering Site Overseas Temporary Tapin District And Career Development has no significant effect on the Performance of PT. The Global Makara Site of the BRE Rantau Technique in Tapin District, all of the independent variables have a significant influence on the variables that are used together (simultaneous), the adjusted determination (R2) is 0.332 or 33.2%, this shows it is supported by those provided by the variables free of the variables they replace.